2017
DOI: 10.1074/jbc.m117.785253
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the epithelial Na+ channel by paraoxonase-2

Abstract: Paraoxonase-2 (PON-2) is a membrane-bound lactonase with unique anti-oxidative and anti-atherosclerotic properties. PON-2 shares key structural elements with MEC-6, an endoplasmic reticulum-resident molecular chaperone in MEC-6 modulates the expression of a mechanotransductive ion channel comprising MEC-4 and MEC-10 in touch-receptor neurons. Because mRNA resides in multiple rat nephron segments, including the aldosterone-sensitive distal nephron where the epithelial Na channel (ENaC) is expressed, we hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
(85 reference statements)
2
11
0
Order By: Relevance
“…This experiment can be interpreted as a modulation of tonical intracellular ROS level that favours our hypothesis that this level is necessary for basal sodium transport. In addition, H 2 O 2 has been shown to inactivate ubiquitination of lung α‐ENaC, thus increasing its surface expression, which is also consistent with the observations of Rochat et al Furthermore, recently Shi et al have reported that membrane expression of ENaC is regulated by paraoxonase‐2 (PON‐2), a membrane‐bound lactonase with unique antioxidative and antiatherosclerotic properties. They have shown that overexpression of PON‐2 reduces channel density at the cell membrane.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This experiment can be interpreted as a modulation of tonical intracellular ROS level that favours our hypothesis that this level is necessary for basal sodium transport. In addition, H 2 O 2 has been shown to inactivate ubiquitination of lung α‐ENaC, thus increasing its surface expression, which is also consistent with the observations of Rochat et al Furthermore, recently Shi et al have reported that membrane expression of ENaC is regulated by paraoxonase‐2 (PON‐2), a membrane‐bound lactonase with unique antioxidative and antiatherosclerotic properties. They have shown that overexpression of PON‐2 reduces channel density at the cell membrane.…”
Section: Discussionsupporting
confidence: 81%
“…They have shown that overexpression of PON‐2 reduces channel density at the cell membrane. However, this study did not rule out the possibility that PON‐2 might modify membrane lipid composition and/or quantity of reactive oxygen species in the setting of oxidative stress, which, thus, might alter ENaC gating as well …”
Section: Discussionmentioning
confidence: 87%
“…The average amiloride-sensitive Na + current in oocytes co-expressing ENaC and PON3 (-1.4 ± 1.4 μA, n=60) is approximately 40% lower than that in oocytes expressing ENaC alone (-2.4 ± 1.8 μA, n=62, p < 0.01). This is similar to the extent of inhibition of PON2 on ENaC activity (57). The inhibitory effect of PON3 is specific to ENaC, as PON3 did not alter the renal outer medullary K + (ROMK) channel activity (-2.5 ± 1.8 μA in oocytes expressing ROMK vs -2.2 ± 1.9 μA in oocytes coexpressing PON3 and ROMK, Fig.…”
Section: Pon3 Inhibits Enac Activity By Reducing Channel Surface Exprsupporting
confidence: 74%
“…Nonetheless, our results using either cultured epithelial cells or Xenopus oocytes support that PON3 decreases ENaC functional expression. Other members of this family, including PON2 and MEC-6, also inhibit ENaC activity in oocytes (57). This negative regulation of channel activity is of great interest to us, as ENaC hyperactivity has physiological consequences (11,13,(98)(99)(100)(101).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation